2022
DOI: 10.1007/s10098-022-02453-4
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic pyrolysis of recycled polypropylene using a regenerated FCC catalyst

Abstract: The increasing generation of plastic wastes forces us to search for final disposal technologies environmentally friendly such as pyrolysis, which becomes an interesting technique because it takes advantage of the wastes obtaining important products. In addition, catalytic pyrolysis by using commercial catalysts, e.g. such zeolites, alumina or recovered from other industrial processes, it allows decreases the activation energy and selectivity in the obtained products. In this study, we report the evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Moreover, this process has the potential to reduce the carbon footprint of plastic products by reducing carbon dioxide and carbon monoxide emissions [ 6 ]. Previous works investigating thermal [ 7 , 8 ] and catalytic [ 9 ] pyrolysis have shown its potential, as well as the optimal operating conditions for the recovery of cleaner energy from plastic waste [ 6 , 10 ] or specific mixtures [ 7 ]. However, there is currently great interest, especially in catalytic pyrolysis, due to its great advantages, which include the following: (i) it accelerates the reaction rate of the process, allowing a greater depolymerization of the raw material; (ii) it reduces the energy necessary for the degradation of plastic waste; and (iii) it provides greater selectivity to obtain higher-quality pyrolytic products [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this process has the potential to reduce the carbon footprint of plastic products by reducing carbon dioxide and carbon monoxide emissions [ 6 ]. Previous works investigating thermal [ 7 , 8 ] and catalytic [ 9 ] pyrolysis have shown its potential, as well as the optimal operating conditions for the recovery of cleaner energy from plastic waste [ 6 , 10 ] or specific mixtures [ 7 ]. However, there is currently great interest, especially in catalytic pyrolysis, due to its great advantages, which include the following: (i) it accelerates the reaction rate of the process, allowing a greater depolymerization of the raw material; (ii) it reduces the energy necessary for the degradation of plastic waste; and (iii) it provides greater selectivity to obtain higher-quality pyrolytic products [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the catalysts used in this process are recycled catalysts from fluid catalytic cracking (FCC) units [ 9 ], red mud [ 13 ], ruthenium homogeneous catalysts [ 14 ], nanocatalysts [ 15 ] and natural or synthetic zeolites [ 16 , 17 ]. Many researchers have shown that zeolites present a greater potential due to their acidic properties, unique pore size, and large surface area, and they are much more active in the catalytic pyrolysis of different thermoplastics such as polypropylene (PP), polystyrene (PS), high-density polyethylene (HDPE), low-density polyethylene (LDPE) and polyvinyl chloride (PVC) to obtain aromatic hydrocarbons [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The calculated values of microporosity show that the microporosity of the regenerated catalyst (49.79%) is higher than that of the fresh and spent catalyst (40.39%) and (49.73%), respectively, which is due to the presence of a large mesopore peak of 318.66 Å created by the effect of regeneration gas flow [1,24,35]. However, based on the values for the surface area and porosity of the regenerated catalyst compared to the values of the spent catalyst, it was found that there is a limit to the inverse relationship between surface area and porosity (the surface area of the catalyst decreases while its porosity increases) [36].…”
Section: N2 Isotherm and Pore Size Distribution Analysismentioning
confidence: 99%